Exploring English Education Students’ Self-Regulated Learning Strategies in Writing English - Sutrisno, Agus; Fiani, Ani; Triyogo, Agus (EDULIA: English Education, Linguistic and Art Journal, 2024)
This study aimed to describe the English education students’ self-regulated learning strategies in writing English at PGRI Silampari University. A descriptive qualitative method was used for this study. The subject of this study was the second-semester English Education Study Program at PGRI Silampari University. The data were taken from the Questionnaire for Self-Regulated Learning Writing Strategies (QSRLWS) for EFL learners. The data were analyzed using Gay and Peter’s qualitative data analysis. The results of this study showed that the second-semester students used metacognitive, cognitive, social, and motivational/affective strategies. However, there were differences in the intensity of writing English. Keywords: Learning Strategies, Self-Regulated Learning, Students, Writing